Two new compounds from Atractylodes macrocephala with neuroprotective activity. Issue 1 (2nd January 2017) - Zhang, Na; Liu, Chao; Sun, Tie-Min; Ran, Xiao-Ku; Kang, Ting-Guo; Dou, De-Qiang
Abstract: In the present study, two new compounds, together with six known compounds, were isolated from rhizome of Atractylodes macrocephala Koidz by a series of silica gel, ODS column chromatography, and preparative HPLC. Their structures were characterized as atractylenolide II (1 ), atractylenolide I (2 ), biepiasterolid (3 ), isoatractylenolide I (4 ), atractylenolide III (5 ), 3 β -acetoxyl atractylenolide I (6 ), (4 E, 6 E, 12 E )-tetradeca-4, 6, 12-triene-8, 10-diyne-13, 14-triol (7 ), (3S, 4 E, 6 E, 12 E )-1-acetoxy-tetradeca-4, 6, 12-triene-8, 10-diyne-3, 14-diol (8 ) on the basis of 1D, 2D NMR, and circular dichroism analyses. Among them, compounds6 and8 were novel compounds. In addition, their neuroprotective activity against MPP + -induced SH-SY5Y cells was evaluated by MTT colorimetry. The results showed that all these compounds have definite protective effect on MPP + -induced SH-SY5Y cells.